2005
DOI: 10.1128/mcb.25.21.9304-9317.2005
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor β2 Is a Neuronal Death-Inducing Ligand for Amyloid-β Precursor Protein

Abstract: APP, amyloid ␤ precursor protein, is linked to the onset of Alzheimer's disease (AD). We have here found that transforming growth factor ␤2 (TGF␤2), but not TGF␤1, binds to APP. The binding affinity of TGF␤2 to APP is lower than the binding affinity of TGF␤2 to the TGF␤ receptor. On binding to APP, TGF␤2 activates an APP-mediated death pathway via heterotrimeric G protein G o , c-Jun N-terminal kinase, NADPH oxidase, and caspase 3 and/or related caspases. Overall degrees of TGF␤2-induced death are larger in ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 53 publications
6
57
0
1
Order By: Relevance
“…In addition, p75NTR and/or PLAIDD, putative cell membrane receptors for Aâ, are able to cause neuronal cell death when ectopically overexpressed (18,44). We have recently demonstrated that TGF â2 is a natural ligand for amyloid-precursor protein (APP) that activates a neuronal cell death signal cascade (20). Based on of this finding and of the reported observation that TGF â2 expression is upregulated by toxic Aâ (21), we have put forward a new paradigm for neuronal cell death relevant to AD.…”
Section: Neuronal-death Mechanismsmentioning
confidence: 99%
“…In addition, p75NTR and/or PLAIDD, putative cell membrane receptors for Aâ, are able to cause neuronal cell death when ectopically overexpressed (18,44). We have recently demonstrated that TGF â2 is a natural ligand for amyloid-precursor protein (APP) that activates a neuronal cell death signal cascade (20). Based on of this finding and of the reported observation that TGF â2 expression is upregulated by toxic Aâ (21), we have put forward a new paradigm for neuronal cell death relevant to AD.…”
Section: Neuronal-death Mechanismsmentioning
confidence: 99%
“…The mNetrin1 cDNA was inserted into the pEF1/MycHis vector (Invitrogen) at the EcoRI and XbaI sites. Mouse WT-APP and V642I-APP cDNAs inserted in the pcDNA3.1/MycHis were described previously (11)(12)(13). The expression vectors for dominant-negative ASK1 and JNK were also described in earlier studies (11)(12)(13).…”
Section: Methodsmentioning
confidence: 99%
“…Cells, Cell Death, and Cell Viability-Neuronal cell death assays related to AD were first performed by Yamatsuji et al (10) and previously described in detail (11)(12)(13)21). Neurohybrid F11 cells were also described earlier (22).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data suggest a scenario in which C31, when removed from APP, abnormally activates or disrupts signaling pathways mediated by APP. One possibility is that the signaling initiated by interaction of the APP C-terminal domain with signal transduction proteins normally is tightly regulated by binding of ligand(s) to its extracellular domain (variously identified as F-spondin [29], Notch [30,31], TGF-β2 [32], and even Aβ [33,34]). In such a scenario, as suggested by McPhie et al, C31, when not attached to APP, is relieved of the normal constraints imposed on it when the extracellular domain of APP is not occupied by a ligand, and becomes constitutively active or else takes on signaling functions that it does not normally possess.…”
Section: Referencementioning
confidence: 99%